The relationship between online learning self-efficacy, informal digital learning of English, and student engagement in online classes: the mediating role of social presence - Wu, Ronglan (Frontiers in Psychology, 2023)
This study examines the relationship between Online Learning Self-Efficacy (OLSE), Informal Digital Learning of English (IDLE), student engagement in online classes, and the mediating role of Social Presence (SP) among intermediate Chinese English as a Foreign Language (EFL) students. The research included 389 participants enrolled in online English courses within a chain of language schools. Data were collected using valid scales to assess OLSE, IDLE, SP, and online student engagement. Structural Equation Modeling (SEM) was used for analysis. The results indicated that OLSE and SP directly influenced online student engagement. Furthermore, IDLE had a positive impact on online student engagement, partly mediated by SP. This suggests that informal digital learning of English plays a crucial role in influencing students' engagement in online classes, facilitated through the sense of social presence experienced by students during virtual interactions. Overall, this research provides valuable insights into the factors affecting student engagement in online learning environments.